ArControl: An Arduino-Based Comprehensive Behavioral Platform with Real-Time Performance - Chen, Xinfeng; Li, Haohong (Frontiers in Behavioral Neuroscience, 2017)
Studying animal behavior in the lab requires reliable delivering stimulations and monitoring responses. We constructed a comprehensive behavioral platform (ArControl: Arduino Control Platform) that was an affordable, easy-to-use, high-performance solution combined software and hardware components. The hardware component was consisted of an Arduino UNO board and a simple drive circuit. As for software, the ArControl provided a stand-alone and intuitive GUI (graphical user interface) application that did not require users to master scripts. The experiment data were automatically recorded with the built in DAQ (data acquisition) function. The ArControl also allowed the behavioral schedule to be entirely stored in and operated on the Arduino chip. This made the ArControl a genuine, real-time system with high temporal resolution (<1ms). We tested the ArControl, based on strict performance measurements and two mice behavioral experiments. The results showed that the ArControl was an adaptive and reliable system suitable for behavioral research.